Maple syrup urine disease due to a paracentric inversion of chr 19 that disrupts BCKDHA: A case report. Issue 6 (20th September 2022) - Yokoi, Katsuyuki; Nakajima, Yoko; Sudo, Yuta; Mariya, Tasuku; Kawamura, Rie; Tsutsumi, Makiko; Inagaki, Hidehito; Yoshikawa, Tetsushi; Ito, Tetsuya; Kurahashi, Hiroki
Abstract: Maple syrup urine disease (MSUD) is a rare autosomal recessive inherited disorder of branched‐chain amino acid metabolism caused by mutations in BCKDHA, BCKDHB, and DBT that encode the E1α, E1β, and E2 subunits of the branched‐chain α‐ketoacid dehydrogenase (BCKD) complex. Various MSUD‐causing variants have been described; however, no structural rearrangements in BCKDHA have been reported to cause the classic MSUD phenotype. Here, we describe the classic patient with MSUD with compound heterozygous pathogenic variants in BCKDHA : a missense variant (NM_000709.3:c.757G > A, NP_000700.1:p.Ala253Thr) and a paracentric inversion disrupting Intron 1 of BCKDHA, which was identified by whole‐genome sequencing and validated by fluorescence in situ hybridization. Using the sequence information of the breakpoint junction, we gained mechanistic insight into the development of this structural rearrangement. Furthermore, the establishment of junction‐specific polymerase chain reaction could facilitate identification of the variant in case carrier or future prenatal/preimplantation tests are necessary.